KORELASI PANJANG LENGAN BAWAH DAN TINGGI BADAN MAHASISWI SUKU BANJAR FAKULTAS KEDOKTERAN UNIVERSITAS LAMBUNG MANGKURAT - Iwan Aflanie; Nurul Qomariah; Mashuri Mashuri (Berkala Kedokteran, 2017)
Abstract: Estimated height has an important role in identifying unknown bodies, incomplete, and the residual bone. Measurements in the long bones such as the forearm are better used to determine the height because it is the best result among the other members of the body size. The purpose of this study was to analyzed a correlation between the forearm length with the height of Banjar Tribe’s students of Medical Faculty of Lambung Mangkurat University and to obtain height estimation formula based on the forearm length in Banjar Tribe’ female. The research method is an analytical observation with cross sectional approach. The research subjects were taken by purposive sampling with samples of 52 people and were analyzed by Pearson correlation and linear regression analysis. The results of Pearson test showed that the value of p = 0,00 for the right and left arm with the value of r = 0.974 for the right arm and r = 0.972 for the left arm, which means there is a very strong relationship between the forearm length with height. It is concluded that there is a very strong correlation between the forearm length with students height of Banjar tribe Medical Faculty of Lambung Mangkurat University with height estimation formula Height = 63,838 + 3,693 x length of the right forearm and Height = 61,873 + 3,780 x left forearm length. Keywords: identification, height estimation, Banjar tribe’ female Abstrak: Memperkirakan tinggi badan mempunyai peranan penting dalam mengidentifikasi jenazah tidak dikenal, tidak lengkap, dan sisa tulang. Pengukuran pada tulang panjang seperti lengan bawah lebih baik digunakan untuk menentukan tinggi badan karena merupakan hasil terbaik diantara ukuran anggota tubuh yang lain. Penelitian ini bertujuan menganalisis korelasi antara panjang lengan bawah dengan tinggi badan dan mendapatkan formula estimasi tinggi badan berdasarkan panjang lengan bawah pada mahasiswi suku Banjar Fakultas Kedokteran Universitas Lambung Mangkurat. Metode penelitian adalah observasional analitik dengan pendekatan cross sectional. Pengambilan subjek penelitian dengan cara purposive sampling dengan jumlah sampel sebanyak 52 orang. Analisis yang digunakan dengan analisis korelasi Pearson. Hasil uji Pearson didapatkan nilai p = 0,00 untuk lengan kanan dan kiri. Hubungan  antara panjang lengan bawah kanan dengan tinggi badan memiliki nilai r = 0,974, sedangkan hubungan  antara panjang lengan bawah kiri dengan tinggi badan memiliki nilai r = 0,972. Kesimpulan penelitian ini adalah terdapat korelasi yang sangat kuat antara panjang lengan bawah dengan tinggi badan pada mahasiswi suku Banjar Fakultas Kedokteran Universitas Lambung Mangkurat dengan formula estimasi tinggi badan TB = 63,838 + 3,693 x panjang lengan bawah kanan dan TB = 61,873 + 3,780 x panjang lengan bawah kiri. Kata-kata kunci : identifikasi, estimasi tinggi badan, wanita suku Banjar